Feedback and Literacy: Investigating the Mediating Role of Ambiguity in texting communication - Chairos Valentino Sibarani; Waldi Marbun; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Language literacy is essential for effective communication, especially in text-based interactions where nonverbal cues are absent. This study aims to explore the mediating role of feedback in clarifying ambiguity in text messages among students. While there is already research on feedback and language literacy, there is a gap regarding how feedback can specifically address ambiguity in digital communication. Using a descriptive survey method, data was collected from 30 students at Medan State University through a questionnaire distributed via WhatsApp. The analysis results show that syntactic ambiguity is the most prevalent type, followed by semantic and referential ambiguity. The findings showed that feedback strategies such as repetition, reformulation, and explicit clarification significantly improved understanding and reduced miscommunication. Students reported that these strategies helped clarify ambiguous messages and encouraged clearer interactions with the lecturer. In conclusion, effective feedback mechanisms are essential for improving communication clarity in text messages, especially in academic contexts. This study underscores the importance of developing feedback literacy among university students to effectively navigate ambiguity, thereby improving their language literacy and overall communication skills. Further research can extend these findings by exploring different contexts and demographics to generalize the results.